The Role of Open Access in Reducing Waste in Medical Research - Glasziou, Paul (Public Library of Science, 2014)
In a guest editorial, Paul Glasziou discusses waste in medical research and how this can be ameliorated through improving post-publication access. Please see later in the article for the Editors' Summary